KEPENTINGAN ISRAEL DALAM KERJASAMA PERDAGANGAN BEBAS DENGAN UNI EMIRAT ARAB (UEA) TAHUN 2022 - Roji, Noval Fahrul; Aufiya, Mohd. Agoes (Indonesian Association for International Relations, 2023)
This study aims to find out the reasons for Israel forming free trade cooperation with the United Arab Emirates (UAE). The research uses a qualitative explanatory method, and uses a literature study method in collecting data. This study also uses Rational Actor Theory as an analytical tool. The results obtained in this study are that Israel forms free trade with the UAE due to economic interests and political interests. Economic interests namely improving the Israeli economy which includes increasing revenue and bilateral trade, and increasing Israeli companies in the UAE. Then Israel's political interests are to further strengthen relations with the UAE, and form a positive image to other Arab countries